Five years after the Liikanen Report: What have we learned? - Martin Götz; Jan Pieter Krahnen; Tobias Tröger (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
The publication of the Liikanen Group's final report in October 2012 was surrounded by high expectations regarding the implementation of the reform plans through the proposed measures that reacted to the financial and sovereign debt crises. The recommendations mainly focused on introducing a mild version of banking separation and the creation of the preconditions for bail-in measures. In this article, we present an overview of the regulatory reforms, to which the financial sector has been subject over the past years in accordance with the concepts laid out in the Liikanen Report. It becomes clear from our assessment that more specific steps have yet to be taken before the agenda is accomplished. In particular, bail-in rules must be implemented more consistently. Beyond the question of the required minimum, the authors develop the notion of a maximum amount of liabilities subject to bail-in. The combination of both components leads to a three-layer structure of bank capital: a bail-in tranche, a deposit-insured bailout tranche, and an intermediate run-endangered mezzanine tranche. The size and treatment of the latter must be put to a political debate that weighs the costs and benefits of a further increase in financial stability beyond that achieved through loss-bearing of the bail-in tranche.
urn:nbn:de:hebis:30:3-452013
Keywords: G18; G21; G28; K22; K23; 330; financial stability; banking separation; prohibition of proprietary trading; banking and treasury functions; bail-in; MREL; TLAC